Is routine preoperative screening echocardiogram indicated in all children with congenital duodenal obstruction? - Short, Scott S. (Pediatr Surg Int, 2014)
INTRODUCTION: Congenital duodenal obstruction (DO) is frequently associated with congenital heart disease (CHD). Operative repair of DO is often postponed until an echocardiogram is completed, which may result in unnecessary delays. We aimed to identify and characterize CHD in children with DO to determine if appropriately selected patients could forego preoperative echocardiogram. METHODS: A two-center retrospective review of all infants with DO undergoing operative repair with completed echocardiograms was included (2003–2011). Demographics, co-morbid conditions, clinical exam findings, radiologic imaging, and need for cardiac surgery were recorded. RESULTS: 67 children were identified. 47 (70.1 %) had CHD on echocardiogram of which 19 (40.5 %) had significant CHD. Children without clinical findings, abnormalities on physical examination, and/or abnormal chest x-ray were unlikely to have CHD; i.e., no asymptomatic child had significant CHD. Sensitivity and specificity of clinical findings, physical exam, and/or chest x-ray for significant CHD were 100 % (95 % CI 0.79–1.0) and 37.5 % (95 % CI 0.24–0.53), respectively, for major CHD and 87.2 % (0.74–0.95) and 60 % (0.36–0.80) for any CHD. CONCLUSION: Careful clinical assessment, evaluation with pulse oximetry, and chest x-ray may be sufficient to exclude significant CHD in children with DO. Identifying children at low risk for cardiac lesions may prevent unnecessary delays to operative intervention and may limit medical expenses.